1995
DOI: 10.1111/j.1365-2303.1995.tb00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of bile canaliculi in long‐term primary cultures of adult rat hepatocytes on permeable membrane: an ultrastructural study

Abstract: Adult rat hepatocytes were cultured for 15 days on type I collagen-coated permeable membranes in a hormonally defined Waxman's modified medium supplemented with very low concentrations of insulin, glucagon and dexamethasone. Phase contrast examination showed that 15-day-old cultures still formed a regular monolayer of polygonal cells. In similarly aged cultures, intracellular glycogen was abundant and evenly distributed, while steatosis remained very limited. Scanning and transmission electron microscopy showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…There also appears to be an interplay between ECM receptor occupancy and cell shape that is essential in maintaining the differentiated polarized hepatocyte phenotype (Singhvi et al, 1994) see Figure 1. Growth of monolayer cultures on collagen-coated permeable membranes (Arterburn et al, 1995;Guery et al, 1995) or in perfused matrix capillary systems (Gerlach et al, 1995) maintain canalicular structures, indicating that nutrient evailability at the basolateral surface also may be a significant factor.…”
Section: Development and Maintenance Ofmentioning
confidence: 98%
“…There also appears to be an interplay between ECM receptor occupancy and cell shape that is essential in maintaining the differentiated polarized hepatocyte phenotype (Singhvi et al, 1994) see Figure 1. Growth of monolayer cultures on collagen-coated permeable membranes (Arterburn et al, 1995;Guery et al, 1995) or in perfused matrix capillary systems (Gerlach et al, 1995) maintain canalicular structures, indicating that nutrient evailability at the basolateral surface also may be a significant factor.…”
Section: Development and Maintenance Ofmentioning
confidence: 98%
“…Monolayer cultures of hepatocytes on extracellular matrix proteins adopt a flat morphology [13,14], and the development of bile canalicular structures in these cultures is rare, heterogeneous, and short-lived [12,15]. Several investigators have reported improved maintenance of archetypal polarity [13,16] and bile canaliculi formation in extracellular matrix sandwich cultures [14,15,17], on collagen-coated porous membranes [18], and in hepatoma-derived hybrid cell lines [19 -21]. However, the restraints of such two-dimensional systems hinder the development of anastomosing channels among many cells.…”
Section: Introductionmentioning
confidence: 99%